2020
DOI: 10.3389/fped.2020.594375
|View full text |Cite
|
Sign up to set email alerts
|

IPEX as a Consequence of Alternatively Spliced FOXP3

Abstract: The transcription factor FOXP3 controls the immunosuppressive program in CD4 + T cells that is crucial for systemic immune regulation. Mutations of the single X-chromosomal FOXP3 gene in male individuals cause the inherited autoimmune disease immune dysregulation, polyendocrinopathy, enteropathy, and X-linked (IPEX) syndrome. Insufficient gene expression and impaired function of mutant FOXP3 protein prevent the generation of anti-inflammatory regulatory T (Treg) cells and fail to inhibit autoreactive T cell re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 96 publications
1
19
0
1
Order By: Relevance
“…Moreover, alternative splicing of FOXP3 controls regulatory T cell effector functions and is associated with human atherosclerotic plaque stability [ 50 ]. Accumulated data also suggest that IPEX syndrome may be a consequence of alternatively spliced FOXP3 [ 51 ]. Finally, FOXP3 isoform profile has been linked to cardiovascular diseases [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, alternative splicing of FOXP3 controls regulatory T cell effector functions and is associated with human atherosclerotic plaque stability [ 50 ]. Accumulated data also suggest that IPEX syndrome may be a consequence of alternatively spliced FOXP3 [ 51 ]. Finally, FOXP3 isoform profile has been linked to cardiovascular diseases [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that patients with IPEX syndrome who have missense mutations and deletions in splicing sites do not have Treg CD4+CD25+Foxp3+ lymphocytes and have a more severe form of the disease. Additionally, the absence of CD4+CD25+ cells confirms the diagnosis [35]. IPEX also has high levels of IgE and IgA immunoglobulins, as well as eosinophilia, which proves that the transcription factor Foxp3 is strongly associated with the human immune response [179][180][181][182].…”
Section: Specialized Researchmentioning
confidence: 74%
“…Two of them, located between amino acids 68-76 and amino acids 239-248, are nuclear export signals which are short peptides containing hydrophobic residues targeted for export from the cell nucleus into the cytoplasm through the nuclear pore complex (Figure 2) [32]. Another example is the LXXLL motif, located between amino acids 92-96, which is involved in many proteinprotein interactions related to various aspects of transcription regulation (Figure 2) [33][34][35]. These motifs are present in many transcription factors and cofactors, mediating interactions that may activate or suppress transcription [36,37].…”
Section: Molecular Characterization Of the Foxp3 Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Two other isoforms, FOXP3Δ2Δ7 and FOXP3Δ7, have also been described in human lymphocytes and epithelial cells, but unlike FOXP3FL and FOXP3Δ2, neither appears to play a role in Treg suppressive activity ( 12 ). Therefore, the need to maintain their expression when restoring a dysregulated immune system, such as that in IPEX patients, is not clear ( 13 , 14 ). In contrast to human T cells, mice express only FOXP3FL ( 15 ).…”
Section: Introductionmentioning
confidence: 99%